Peran Guru Dalam Pembelajaran Pada Sekolah Dasar Negeri 70 Manado - Anita Sarah Meiske Femmy Mingkid; Roos M.S. Tuerah; Marien Pinontoan; Jeanne Mangantung; Telma M. Tiwa (Peneliti.net, 2022)
This study aims to determine the role of teachers as educators, instructors, and trainers in learning at SD Negeri 70 Manado. This type of research is a qualitative descriptive method. Research data sources consist of primary data sources and secondary data sources. Primary data were obtained from interviews with homeroom teachers as informants to determine the role of teachers as educators, teachers, and trainers in learning. The research site is at SD Negeri 70 Manado. Data collection techniques are observation, interviews and documentation. The data analysis technique is based on the theory of Miles and Huberman with a sequence of steps for data reduction, data presentation, and drawing conclusions. The validity of the data is done through triangulation of sources, techniques and time. The results of this study indicate that (1) Teachers of SD Negeri 70 Manado are known to have a role in educating students responsibly in developing the potential of students in the affective, cognitive, and psychomotor domains, as well as having sincere and sincere feelings in educating and making students comfortable to come to school and comfortable in learning, (2) Teachers at SD Negeri 70 Manado have a role to teach in providing information related to knowledge to students so that it can be understood easily for students, (3) Teachers at SD Negeri 70 Manado is known to have a role in training students to develop the interests and talents that exist within students, so that they can be used for good things in the school environment and outside the school environment.